Analisis Strategi Pemasaran Menggunakan SWOT pada Zeze Media - Haniyatus Sofiah Anggraini (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Zeze Media is a stationery and printing service store located in Balung District, Jember Regency. During its journey, this business has experienced several obstacles such as seasonal sales, changes in consumer behavior towards digital, and limited human resources that have an impact on service quality. Zeze Media needs to develop an appropriate marketing strategy to face these obstacles so that it can survive and increase its competitiveness. This study aims to analyze Zeze Media's marketing strategy using the SWOT method with the strategic management theory of Hunger and Wheleen, so that the strengths, weaknesses, opportunities, and threats faced can be identified. The research method used is a qualitative approach with data collection techniques in the form of interviews with the director and head of sales, questionnaires to employees, direct observation on site, and documentation in the form of photos, product catalogs, and promotional materials. The collected data were analyzed using a SWOT matrix to determine the business position and the right strategy. The results show that Zeze Media is in Quadrant I of the SWOT diagram with an IFAS value of 2.319 on the X-axis of the SWOT diagram and an EFAS value of 1.757 on the Y-axis of the SWOT diagram. This position demonstrates Zeze Media's ability to maximize its strengths to capitalize on market opportunities. The strategy it can implement is a growth-oriented one. Zeze Media has been able to integrate the company's internal strengths with existing external opportunities. Zeze Media leverages its various potentials, such as a diverse range of stationery products, strong relationships with loyal customers, and fast service in the photocopying and printing sectors, to increase its competitiveness and expand its market reach amidst increasingly fierce competition.
Reuploud file repositori 29 Jan 2026_Yudi
Keywords: Marketing Strategy; SWOT; Zeze Media; Quadrant I